INFLUENCE OF DIFFERENT CATEGORIES OF FOLLICLES AND PRESENCE OF CL ON RECOVERY RATE, QUALITY AND QUANTITY OF BUFFALO OOCYTES - MAKWANA, P M; SHAH, R G; SINGH, R P; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 408 freshly collected abattoir ovaries of Surti buffalo during peak breedingseason. The total number of follicles recorded on these ovaries was 1369 and the overall mean number of folliclesper ovary was found to be 3.36 ± 0.08. The mean number (percentage) of small, medium and large size follicles perovary were 1.33 ± 0.05 (39.66), 1.32 ± 0.05 (39.44) and 0.70 ± 0.04 (20.89), respectively. Oocytes collected byslicing method were classified on the basis of cumulus investment and ooplasm homogeneity, viz., grade A (>3layer of cumulus cells), grade B (1-3 layerof cumulus cells), grade C (less compact cumulus) and grade D (nudeoocytes). The mean number of oocytes per ovary of grade A (0.82 ± 0.04) and B (0.79 ± 0.04) were significantlyhigher (P
Keywords: Follicles; Corpus luteum; Recovery rate; Cumulus cells; Oocytes